(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
This paper evaluated the effectiveness of the progressive relaxation for the control of the anxiety and hopelessness in patients suffering from cancer. Thirty women, age between 20 and 60 years, took part in the research. The level of anxiety and hopelessness of each participant was evaluated through Beck’s Hopelessness Scale (BHS) and Beck’s Anxiety Inventory (BDI) administered before and after relaxation. The intervention lasted 8 weeks and included no-directive interview, the application of the scales for the establishment of baseline, relaxation and the re-administration of the scales. The ANOVA confirms that the relaxation was capable to lower the average scores in 9.3 points (BAI) and .98 point (BHS), but this effect did not last along the weeks.